2012
DOI: 10.1530/rep-12-0030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on follicular function may be relieved by exogenous gonadotropin treatment in a sheep model

Abstract: The current study investigated hormonal and ovarian changes during physiological reproductive aging in Sarda ewes. In a first experiment, follicular and corpus luteum dynamics were compared during an induced oestrus cycle in aged (12-14 years) and young adult ewes (4-5 years). Oestrus cycle characteristics did not differ between the two experimental groups. However, follicular function during the follicular phase showed significant alterations in aged ewes, as determined by a lack of dominance effect and by lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…There was a trend for a greater proportion of MNO to be recovered from aspiration in young than from old alpacas. This is likely due to the fact that females undergoing physiological reproductive aging experience a decrease in oocyte quality and developmental competence (Berlinguer et al 2012, Malhi et al 2007. In horses, sheep and cattle, it has been demonstrated that oocytes recovered from aged animals and deemed suitable for incubation were less likely to achieve maturation than those collected from young animals (Berlinguer et al 2012, Brinsko et al 1995.…”
Section: Chapter 4: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a trend for a greater proportion of MNO to be recovered from aspiration in young than from old alpacas. This is likely due to the fact that females undergoing physiological reproductive aging experience a decrease in oocyte quality and developmental competence (Berlinguer et al 2012, Malhi et al 2007. In horses, sheep and cattle, it has been demonstrated that oocytes recovered from aged animals and deemed suitable for incubation were less likely to achieve maturation than those collected from young animals (Berlinguer et al 2012, Brinsko et al 1995.…”
Section: Chapter 4: Resultsmentioning
confidence: 99%
“…This is likely due to the fact that females undergoing physiological reproductive aging experience a decrease in oocyte quality and developmental competence (Berlinguer et al 2012, Malhi et al 2007. In horses, sheep and cattle, it has been demonstrated that oocytes recovered from aged animals and deemed suitable for incubation were less likely to achieve maturation than those collected from young animals (Berlinguer et al 2012, Brinsko et al 1995. In sheep, the proportion of morphologically abnormal oocytes was significantly higher in aged animals (Berlinguer et al 2012).…”
Section: Chapter 4: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase 1 aimed at determining the lowest doses of glycerol as a titration feeding trial able to modify ewe's metabolic status, as previously described using a high dose (20), without impacting on RBC indices. Glycerol was administered both alone and in combination with propylene glycol, as previously described (10,19,20).…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasonographic examinations were carried out using a Mylab-alpha (Esaote, Italia) fitted to an endocavitary transducer (8)(9)(10)(11). Each ovarian follicular population was scanned using both Thereafter, on day 14 ovulation rates were determined by counting the corpora lutea present in each ovary by transrectal ultrasonography with a real-time B-mode scanner (Aloka102 SSD 500; Aloka Co., Tokyo, Japan) fitted with a 7.5MHz linear-array probe.…”
Section: Ovarian 3d Ultrasound Scanningmentioning
confidence: 99%